LNA-i-miR-221 activity in colorectal cancer: A reverse translational investigation - Asad Ali; Katia Grillone; Serena Ascrizzi; Giulio Caridà; Lucia Fiorillo; Domenico Ciliberto; Nicoletta Staropoli; Pierosandro Tagliaferri; Pierfrancesco Tassone; Maria Teresa Di Martino (Elsevier, 2024)
Colorectal cancer (CRC) is one of the most common malignancies and a relevant cause of cancer-related deaths worldwide. Dysregulation of microRNA (miRNA) expression has been associated with the development and progression of various cancers, including CRC. Among them, miR-221 emerged as an oncogenic driver, whose high expression is associated with poor patient prognosis. The present study was conceived to investigate the anti-CRC activity of miR-221 silencing based on early clinical data achieved from a first-in-human study by our group. Going back from bedside to bench, we demonstrated that LNA-i-miR-221 reduces cell viability, induces apoptosis in vitro, and impairs tumor growth in preclinical in vivo models of CRC. Importantly, we disclosed that miR-221 directly targets TP53BP2, which, together with TP53INP1, is known as a positive regulator of the TP53 apoptotic pathway. We found that (1) both these genes are overexpressed following miR-221 inhibition, (2) the strong anti-tumor activity of LNA-i-miR-221 was selectively observed on TP53 wild-type cells, and (3) this activity was reduced in the presence of the TP53-inhibitor Pifitrin-α. Our data pave the way to further investigations on TP53 functionality as a marker predictive of response to miR-221 silencing, which might be relevant for clinical applications.